A Study on the Education Supply Chain for Graduate Employability in Bangladesh's Higher Education System - Chowdhury, Rashed; Habib, Md. Mamun (ExcelingTech, 2025)
This research examines the role of Educational Supply Chain Management (EduSCM) in enhancing graduate employability within Bangladesh's higher education system. Despite significant growth in the number of graduates, a skills gap persists, with many graduates facing underemployment or unemployment due to a mismatch between academic knowledge and industry demands. Through a mixed-methods approach combining qualitative insights from university administrators, faculty, industry professionals, and graduates with quantitative survey data from 300 participants, this study explores how aligning curriculum design, faculty quality, university infrastructure, and industry collaboration can improve graduate preparedness for the workforce. The findings reveal a notable disconnect between academic programs and industry needs, with curriculum relevance, faculty industry experience, and industry collaboration identified as key factors influencing employability. The study proposes actionable recommendations, including curriculum reform, enhanced industry partnerships, faculty development, and infrastructure modernization, to bridge the skills gap and improve the employability of graduates. By applying the EduSCM model, this research provides valuable insights for universities, policymakers, and industry stakeholders to optimize higher education and align it with labor market demands, contributing to Bangladesh’s economic growth and sustainable development.